If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(14p + -15q) = 0 (14p * 4 + -15q * 4) = 0 (56p + -60q) = 0 Solving 56p + -60q = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '60q' to each side of the equation. 56p + -60q + 60q = 0 + 60q Combine like terms: -60q + 60q = 0 56p + 0 = 0 + 60q 56p = 0 + 60q Remove the zero: 56p = 60q Divide each side by '56'. p = 1.071428571q Simplifying p = 1.071428571q
| 2x^2+3x-94=0 | | 2x^2-3x+94=0 | | 2x+10=4x-2 | | 4x^2+16x-36=0 | | 4x+3=75 | | 17ab-5a-2ab-3a= | | 5k-5/k+1 | | 2x^2-14x-7=0 | | y=0.70x+7 | | 3(8g-2)=9(5g-10) | | 0.03(4c-56)=-0.6(c-2) | | 5h+5v=r | | 5h+5v=2 | | 0,185xx=43734 | | 0,47xx=141 | | 5t^2-16=16t | | x^2/6=11 | | 6x^2-35x+48=0 | | 2p^3-6p^2-20p=0 | | 4x-4=4m | | 18y^3-3y^2-9y=0 | | (12/13)t+(3/26)=(81/78) | | 6l+5w-9h=5 | | x=(144/55)*(11/12) | | t=(144/55)*(11/12) | | 4v^2-9=0 | | (x-4)(x^2-2x-3)=0 | | 5a+2=12 | | 100a-50=30 | | 6y^2+y-1=0 | | 48x^3-40x^2+40x= | | x-y=2x+y |